2013
DOI: 10.1016/j.neuroimage.2012.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetization transfer imaging of human brain at 7 T

Abstract: Quantitative magnetization transfer (qMT) imaging yields indices describing the interactions between free water protons and immobile macromolecular protons. These indices include the macromolecular to free pool size ratio (PSR), which has been shown to be correlated with myelin content in white matter. Because of the long scan times required for whole-brain imaging (≈20–30 min), qMT studies of the human brain have not found widespread application. Herein, we investigated whether the increased signal-to-noise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
86
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 50 publications
13
86
0
1
Order By: Relevance
“…Values of between 2.4 and 2.0 s −1 were found in the corpus callosum ROI at 3 T and 7 T respectively, which is on the low end of the 2.5–4 s −1 range reported in literature (Sled, Levesque et al 2004, Yarnykh and Yuan 2004, Samsonov, Alexander et al 2012, Dortch, Moore et al 2013). In part, this may be related to methodological differences.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Values of between 2.4 and 2.0 s −1 were found in the corpus callosum ROI at 3 T and 7 T respectively, which is on the low end of the 2.5–4 s −1 range reported in literature (Sled, Levesque et al 2004, Yarnykh and Yuan 2004, Samsonov, Alexander et al 2012, Dortch, Moore et al 2013). In part, this may be related to methodological differences.…”
Section: Discussionmentioning
confidence: 56%
“…The distinctly different T 1 relaxation between grey and white matter has been attributed on their different myelin content: myelin rich white matter contains an up to 30% fraction of proteins and lipids (Randall 1938), whose largely invisible hydrogen ( 1 H) protons exhibit rapid T 1 relaxation (Deese, Dratz et al 1982, Ellena, Hutton et al 1985, Du, Sheth et al 2014) and, through magnetization transfer, accelerate T 1 relaxation of MRI visible water 1 H protons (WP’s). Thus, study of T 1 relaxation with inversion recovery may allow quantification of this magnetization transfer (MT) (Edzes and Samulski 1977, Gochberg and Gore 2003, Dortch, Moore et al 2013) and aid in determining brain myelin content (Stuber, Morawski et al 2014), which has important neuro-scientific and clinical applications (Dinse, Waehnert et al 2013). MRI techniques such as MP2RAGE (Van Gelderen, Koretsky et al 2006, Marques, Kober et al 2010) and DESPOT1 (Deoni, Rutt et al 2008) have recently been proposed and are increasingly being used for this purpose (Dinse, Hartwich et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…B 0 inhomogeneities were mapped using a dual-echo gradient echo sequence (25), with TR/TE 1 /TE 2 = 25/2.3/4.6 ms, excitation flip angle of 25°, SENSE = 1.3, and N EX = 1. T 1 data were acquired using an inversion recovery pulse with turbo-field-echo (TFE) readout (26), followed by a train of saturation pulses and a reduced pre-delay (TD) of 1.5 s (27), where TD is the time from the last saturation pulse to the inversion pulse. Seven inversion-recovery time (TI) points were collected, with TI = 50, 100, 200, 500, 1000, 2000, and 6000 ms.…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the efficiency covering k-space, the readout of the sequence was changed to reduce the scan time for anatomical MT imaging of the human brain at 7T (Dortch et al, 2013;Mougin et al, 2010). In these studies, turbo field-echo readout (TFE; or MPRAGE) was used to more efficiently cover the k-space than conventional MT imaging method.…”
Section: Introductionmentioning
confidence: 99%
“…(R2.14) Recently, Dortch et al demonstrated whole brain covered qMT imaging at 7T. Although they improved the efficiency covering kspace by using TFE readout, the acquisition time was relatively long for routine patient scan (Dortch et al, 2013). Using a fast image acquisition technique such as Simultaneous MultiSlice (Feinberg and Setsompop, 2013) or an EPI readout sequence may allow qMT imaging to be performed in a reasonable scan time; this subject should be assessed in future studies.…”
mentioning
confidence: 99%